Sharing Unverified Information among Generation Z: The Role of Institutional Trust and Self-Efficacy - Muhammad Nabil Syafiq; Kunto Adi Wibowo (Institut Komunikasi dan Bisnis LSPR, 2026)
The widespread circulation of unverified information on social media indicates that trust in information sources does not always prevent the spread of misinformation. This condition raises questions about the role of trust in institutions and individuals’ confidence in detecting misinformation in shaping the tendency to share information on social media. This study aims to examine the direct relationships between trust in institutions on social media, perceived self-efficacy in detecting misinformation, and reasons for sharing unverified information among Generation Z in Indonesia through three explanatory hypotheses. Specifically, this study explores the role of perceived self-efficacy in detecting misinformation as a mediating mechanism in this relationship. Using a survey approach, this study involves 140 Generation Z in Indonesia who are active social media users, to understand how trust in institutions on social media influences individuals’ confidence in detecting misinformation and their reasons for sharing unverified information in online environments. The results show that trust in institutions on social media has no significant effect on reasons for sharing unverified information, whereas perceived self-efficacy in detecting misinformation has a positive and significant effect on the sharing of unverified information.